The Influence of Supervision and Leadership on Employee Work Discipline in Curug District Serang City - Sutihat, Sutihat; Wahyuni, Asti Dian Sri; Komalasari, Komalasari; Maliki, Budi Ilham (Universitas Tanjungpura, 2024)
Discipline leads to higher work performance, discipline is the most important operational function of human resource management. The absence of effective staff discipline will be a challenge for the company to achieve maximum results. It is a challenge for business organizations to achieve optimal performance without strong employee discipline. The aim of this research is to determine the partial influence of supervision and management on employee performance in Curug District, Serang City. A quantitative approach using survey methods is the research methodology used. The population studied was Curug District employees, totaling 45 people, with the number determined using a saturated sampling technique of 45 samples. _a total of 45 employees in Curug District, Serang City, with the number determined using a saturated sampling technique of 45 samples. The research results show that partial supervision has no effect on employee work discipline and leadership partially has an effect on employee work discipline.